Medical neuroscience Q&A - Das, Manas; Baugh, Lee A. (Thieme test prep for the USMLE, 2019)
"Thieme Test Prep for the USMLE: Medical Neuroscience by Manas Das and Lee Baugh fills a void in available board prep materials with its focus on neuroscience. Readers will learn to recall, analyze, integrate, and apply biochemical and molecular biological knowledge to solve clinical problems. Key Highlights ʺ Approximately 520 USMLE-style multiple choice questions on neuroscience, classified as easy, moderate, and difficult, with detailed explanations ʺ Questions cover clinical neurology as well as basics of neuroscience such as development, structure, and function ʺ Chapters are organized based on neuroanatomical structure and systems, from the spinal cord to the automatic nervous system ʺ Neuroimaging section and final exam chapter are invaluable tools for students to utilize before the boards ʺ Questions begin with a clinical vignette, and approximately 35% are image-based, mirroring the USMLEʼ format This essential resource will help you assess your knowledge and fully prepare for the USMLE Step 1 or COMLEX Level 1 exam"...Provided by publisher